Fluorescence-Based Measurements of Membrane-Bound Angiotensin Converting Enzyme 2 Activity Using Xenopus Laevis Oocytes - Luise Fast; Richard Ågren; Hugo Zeberg (Biosensors, 2022)
Functional investigations of enzymes involving cellular expression systems are important for pharmacological studies. The precise control of expression is challenging in transiently transfected mammalian cell lines. Here, we explored the ability of Xenopus laevis oocytes to express a membrane-bound enzyme for functional characterization using standard 96-well plates and a fluorescence-based plate reader assay. We microinjected oocytes with cRNA encoding the angiotensin converting enzyme 2 (ACE2) and measured the enzymatic activity in single oocytes using a commercial fluorescence-based assay. The injected oocytes showed up to a 50-fold increase in fluorescence compared to uninjected oocytes. This fluorescence intensity was dose-dependent on the amount of ACE2 cRNA. These results suggest that Xenopus oocytes can be used for the functional evaluation of membrane-bound enzymes, decreasing the experimental workload.